Performance analysis of asymmetrical less‐rare‐earth permanent magnet motor for electric vehicle - Bingchang Lv; Liwei Shi; Lintao Li; Kaiwen Liu; Jianning Jing (IET Electrical Systems in Transportation, 2022)
Abstract To reduce the manufacturing cost, the cogging torque and the torque ripple of the traditional V‐shaped permanent magnet motor (TPMM), an asymmetrical less‐rare‐earth permanent magnet motor (ALREPMM) is proposed. An equivalent air‐gap flux density model is established, the model is employed to calculate the analytical expression of the no‐load back‐EMF, and the multiple objectives optimisation are carried out for the motor parameters based on the Taguchi algorithm. Electromagnetic performance of the TPMM structure and the ALREPMM structure is compared by finite element method‐based simulation. It is shown that the ALREPMM structure can reduce the amount of rare‐earth materials by 19%, and the cogging torque and the THD values of no‐load back‐EMF are reduced by 77.3% and 26.8%, respectively. Finally, a prototype is manufactured, thus verifying the rationality of the design of the ALREPMM structure through experiments.